2007
DOI: 10.1007/s11423-007-9067-0
|View full text |Cite
|
Sign up to set email alerts
|

Why is externally-facilitated regulated learning more effective than self-regulated learning with hypermedia?

Abstract: We examined how self-regulated learning (SRL) and externally-facilitated selfregulated learning (ERL) differentially affected adolescents' learning about the circulatory system while using hypermedia. A total of 128 middle-school and high school students with little prior knowledge of the topic were randomly assigned to either the SRL or ERL condition. Learners in the SRL condition regulated their own learning, while learners in the ERL condition had access to a human tutor who facilitated their self-regulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
151
0
13

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 295 publications
(194 citation statements)
references
References 42 publications
(68 reference statements)
4
151
0
13
Order By: Relevance
“…Research into the effects of metacognitive scaffolds has only occasionally been used to support metacognitive activities of individuals in innovative learning arrangements (Azevedo and Hadwin 2005;Azevedo et al 2008;Bannert 2006, Bannert et al 2009Lin and Lehman 1999;Veenman et al 2005). The main results from these studies are that scaffolding can increase problem-solving , domain knowledge (Azevedo et al 2008) and transfer of domain knowledge (Bannert 2006, Bannert et al 2009Lin and Lehman 1999).…”
Section: Scaffolding In Innovative Learning Arrangementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research into the effects of metacognitive scaffolds has only occasionally been used to support metacognitive activities of individuals in innovative learning arrangements (Azevedo and Hadwin 2005;Azevedo et al 2008;Bannert 2006, Bannert et al 2009Lin and Lehman 1999;Veenman et al 2005). The main results from these studies are that scaffolding can increase problem-solving , domain knowledge (Azevedo et al 2008) and transfer of domain knowledge (Bannert 2006, Bannert et al 2009Lin and Lehman 1999).…”
Section: Scaffolding In Innovative Learning Arrangementsmentioning
confidence: 99%
“…Research, however, has shown that students lack the metacognitive skillfulness to perform the required regulation and that metacognitive scaffolds can support the regulation of their learning . Findings of studies into the effects of metacognitive scaffolding have shown that scaffolding can improve the learning outcomes of individual learners in innovative learning arrangements (Azevedo and Hadwin 2005;Azevedo et al 2008;Bannert 2006, Bannert et al 2009Lin and Lehman 1999;Veenman et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Self-regulated learning can occur at different levels, from learners controlling how long they engage in studying a given task or whether they want to restudy it (Karpicke, 2009;Metcalfe, 2009;Thiede & Dunlosky, 1999), to learners controlling what information they want to study (e.g., in a hypermedia learning environment; Azevedo, 2005;Azevedo & Cromley, 2004;Azevedo, Moos, Greene, Winters, & Cromley, 2008) or what learning tasks they want to work on (Corbalan, Kester, & Van Merriënboer, 2008;Kostons, Van Gog, & Paas, 2010;Ross, Morrison, & O'Dell, 1989). This article focuses on self-regulated learning in which learners can choose their own learning tasks.…”
Section: Introductionmentioning
confidence: 99%
“…This article focuses on self-regulated learning in which learners can choose their own learning tasks. Research has shown that having control over what information to study or what tasks to work on is not effective for novices' self-regulated learning (Azevedo et al, 2008;Goforth, 1994;Lawless & Brown, 1997;Niemiec, Sikorski, & Walberg, 1996;Williams, 1996). We assume that this may be due to novices' lack of self-assessment and task-selection skills, which play a crucial role in this kind of self-regulated learning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation